Biogas - Recent Advances and Integrated Approaches 2021
DOI: 10.5772/intechopen.86133
|View full text |Cite
|
Sign up to set email alerts
|

Partial Oxidation of Methane to Methanol on Cobalt Oxide-Modified Hierarchical ZSM-5

Abstract: Conversion of methane to more reactive compounds such as methanol has drawn attention for many years. Hierarchical ZSM-5 zeolite has been used as support of metal oxide catalyst to facilitate the partial oxidation of methane to methanol. The NaZSM-5 zeolite was synthesized hydrothermally using double-template techniques, in which tetrapropylammonium hydroxide (TPAOH) and polydiallyldiammonium chloride (PDDA) were used as primary and secondary templates, respectively. HZSM-5 was prepared through multiple NH4 + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…89-1421. 46,47 The synthesized sample showed exact ZSM-5 XRD patterns, with no other impurity peak observed, highlighting the high purity of the products. On the other hand, the ZSM-5 product showed the strong driving action of silica in zeolite crystallization.…”
Section: Resultsmentioning
confidence: 84%
“…89-1421. 46,47 The synthesized sample showed exact ZSM-5 XRD patterns, with no other impurity peak observed, highlighting the high purity of the products. On the other hand, the ZSM-5 product showed the strong driving action of silica in zeolite crystallization.…”
Section: Resultsmentioning
confidence: 84%
“…This activation process is carried out by heating using NH4 + , where on heating it will become NH3 vapor and allow H + to bind to ZSM-5 to form H-ZSM-5. The loss of Na cations produces more templates or pores thereby increasing catalytic activity 23,32 . In contrast to dealumination, the dealumination process not only increases the catalyst surface area to 166 m 2 /g in HZSM-5 Hierarchy but also increases the pore radius to 1,591 and clarifies the micro, meso, and macro pore levels with a high number of mesopores, so it can be said to be a hierarchical process succeed.…”
Section: š· = K Ī» š›½ Cos šœƒmentioning
confidence: 99%
“…Moreover, Krisnandi et al 8) reported Co-oxide modified ZSM-5 were prepared through wet impregnation method. Incipient wet impregnation is the most common way of introducing selective metals to catalysts, particularly on mesoporous supports (pore width 2-50 nm).…”
Section: Introductionmentioning
confidence: 99%